Analisis Swamedikasi Tingkat Pengetahuan, Sikap, Dan Praktik Masyarakat Terhadap Obat Diare Di Klinik Mustopa Cilame - Indi Yutina; Dewi Wulantresna (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Diarrhea is a health issue frequently managed through self-medication. The success of self-medication depends on the public's knowledge, attitudes, and practices regarding the rational use of antidiarrheal drugs. This study aimed to analyze the public's knowledge, attitudes, and practices concerning antidiarrheal self-medication, as well as the relationships and influences between these variables at the Mustopa Cilame Clinic. A quantitative method with a descriptive-analytic design was employed. Sixty respondents were selected using simple random sampling. Data were collected via a questionnaire that had passed validity and reliability testing (Cronbach's Alpha = 0.810). The results indicated that the majority of respondents fell into the "moderate" category for knowledge (45%), attitude (46.7%), and practice (41.7%). Correlation analysis revealed positive and significant relationships between knowledge and attitude (r = 0.588), knowledge and practice (r = 0.551), and attitude and practice (r = 0.510) (p < 0.05), all with moderate strength. Regression analysis showed that knowledge significantly influenced attitude (R² = 0.346; p < 0.001), while attitude significantly influenced practice (R² = 0.260; p < 0.001). It is concluded that better knowledge and more positive attitudes among patients encourage more rational self-medication practices with antidiarrheal drugs in the community.